Computational analysis uncovers the deleterious SNPs along with the mutational spectrum of p53 gene and its differential expression pattern in pan-cancer - Alam, Saruar (2023)
The polymorphism data are available in several databases. NCBI dbSNP houses extensive data for different genes, and NCBI has the largest database that helps analyze single nucleotide polymorphisms. 581 SNPs have been found for cellular tumor antigen p53 (NCBI Reference Sequence: NP_000537.3). Among them, 420 SNPs were found to be missense or non-synonymous. Among 581, there were 435 SNPs in 3′UTR and 112 in 5′UTR regions. Only the missense, 3′ (3 prime), and 5′ (5 prime) UTR SNPs have been selected for further analysis.